A Typology of Emerging Market SMEs' COVID‐19 Response Strategies: The Role of TMTs and Organizational Design. (16th February 2022) - Puthusserry, Pushyarag; King, Timothy; Miller, Kristel; Khan, Zaheer
Abstract: The unique challenges posed by COVID‐19 call for new insights into how firms respond to multiheaded and multistage evolving global crises. Whilst prior research acknowledges the potential role flexible organizational designs and top management teams (TMTs) have for crisis management, these bodies of literature have evolved separately with limited cross‐fertilization. In this study, we seek to provide a contextualized explanation of research phenomena by drawing upon multiple layers of context – namely the environment, TMT and organisational context. Our findings provide vital insights into how emerging market Indian SMEs' organizational designs and TMT configurations led to differential COVID‐19 crisis response strategies. We develop a typology that identifies four strategic responses and illustrate that not all emerging market SMEs are vulnerable at the time of crisis. Our findings extend knowledge on how emerging market SMEs can navigate external shocks such as those caused by COVID‐19. In particular, our research has implications for policymakers and emerging market firms seeking to understand and implement effective organizational designs and policies that can weather the current COVID‐19 pandemic, as well as future multiheaded and multistage black swan crises.